The Increased Expression of Integrin α6 (ITGA6) Enhances Drug Resistance in EVI1high Leukemia - Yamakawa, Norio; Kaneda, Kazuko; Saito, Yusuke; Ichihara, Emi; Morishita, Kazuhiro (PLOS ONE, 2012)
Ecotropic viral integration site-1 (EVI1) is one of the candidate oncogenes for human acute myeloid leukemia (AML) with chromosomal alterations at 3q26. High EVI1 expression (EVI1high) is a risk factor for AML with poor outcome. Using DNA microarray analysis, we previously identified that integrin α6 (ITGA6) was upregulated over 10-fold in EVI1high leukemia cells. In this study, we determined whether the increased expression of ITGA6 is associated with drug-resistance and increased cell adhesion, resulting in poor prognosis. To this end, we first confirmed the expression pattern of a series of integrin genes using semi-quantitative PCR and fluorescence-activated cell sorter (FACS) analysis and determined the cell adhesion ability in EVI1high leukemia cells. We found that the adhesion ability of EVI1high leukemia cells to laminin increased with the increased expression of ITGA6 and integrin β4 (ITGB4). The introduction of small-hairpin RNA against EVI1 (shEVI1) into EVI1high leukemia cells reduced the cell adhesion ability and downregulated the expression of ITGA6 and ITGB4. In addition, the overexpression of EVI1 in EVI1low leukemia cells enhanced their cell adhesion ability and increased the expression of ITGA6 and ITGB4. In a subsequent experiment, the introduction of shRNA against ITGA6 or ITGB4 into EVI1high AML cells downregulated their cell adhesion ability; however, the EVI1high AML cells transfected with shRNA against ITGA6 could not be maintained in culture. Moreover, treating EVI1high leukemia cells with neutralizing antibodies against ITGA6 or ITGB4 resulted in an enhanced responsiveness to anti-cancer drugs and a reduction of their cell adhesion ability. The expression of ITGA6 is significantly elevated in cells from relapsed and EVI1high AML cases; therefore, ITGA6 might represent an important therapeutic target for both refractory and EVI1high AML.